Silver, silicon co-substituted hydroxyapatite modulates bacteria-cell competition for enhanced osteogenic function. (31st August 2021) - Lim, Poon Nian; Wang, Zuyong; Tong, Shi Yun; Ho, Bow; Wang, Wilson; Aizawa, Mamoru; Yang, Zhijie; Thian, Eng San
Abstract: Combating bacteria while promoting tissue regeneration is an aim of highest priority for employing biomaterials in orthopedics that often embroiled with pre-operative contamination. Through simulating a surgical site infection environment and an infected implant site, we showcase the ability of a functionally modified hydroxyapatite, Ag, Si-HA that permits preferential adhesion of human bone marrow derived mesenchymal stem cells (BMSCs) over co-cultured bacterial pathogen, Pseudomonas aeruginosa, by displaying immediate suppression and killing of the bacteria present with minimum cytotoxicity for 28 d. And, at the same time, Ag, Si-HA stimulates BMSCs towards osteogenic differentiation despite being within the contaminated milieu. These findings provide well-defined requirements for incorporating antibacterial properties to biomaterials in managing pre-operative contamination. In addition, it highlights the dual positive attributes of Ag, Si-HA as an effective antibacterial biomaterial and at the same time, promotes bone tissue regeneration.